Implementation of the Single Exponential Smoothing Forecasting Method for Product Sales Prediction at UD XYZ - Wiguna, Deny Arya; Manurung, Nuriadi; Latiffani, Chitra (Universitas Budi Darma, 2025)
In the competitive world of business, demand forecasting is a critical aspect of inventory management. Errors in estimating demand can result in various negative impacts, such as excess inventory that increases storage costs or stock shortages that can lead to lost sales opportunities. UD. Haili often faces challenges in managing inventory due to unpredictable fluctuations in demand. In some cases, demand for certain products experiences sudden spikes, while at other times demand drops sharply. This creates the risk of inventory imbalances, leading to increased operational costs and the potential loss of customers. The objective of this study is to apply the single exponential smoothing (SES) method in forecasting demand for goods so that the forecasting results can provide strategic recommendations for UD. Haili in managing inventory based on the forecasting results. The forecasting results using the developed forecasting application indicate that round shrimp paste has the smallest MAPE, using an alpha of 0.4 with 1.26%, square shrimp paste uses an alpha of 0.1 with 1.98%, and triangular shrimp paste uses an alpha of 0.1 with 4.53%.